Brain Shift Patterns: Upward, Lateral and Downward Herniation, Its Correlation with Clinical Patterns in Acute Intracranial Pathologies and Management - Said Mogutham, Nur Nazleen; Abdullah, Jafri Malin; Omar, Suzuanhafizan; Sa’uadi, Mohammad Iskandar; Syed Jaafar, Sharifah Nawal (Malaysian Journal of Medical Sciences, 2025)
Brain shift represents a critical radiological indicator of intracranial mass effect, reflecting displacement of neural structures due to hematoma, tumour, infarction, or cerebral oedema. Depending on the direction of displacement, brain herniation may manifest as downward (transtentorial), upward (reverse transtentorial), or lateral (midline) shifts (MLSs). Understanding these patterns and their correlation with neurological deterioration remains vital for timely diagnosis and management. The purpose of this analysis is to classify brain shift patterns — downward, lateral, and upward transtentorial herniations — and to correlate radiological findings with clinical parameters including level of consciousness, Glasgow Coma Scale (GCS), pupillary size and reactivity, and predicted intracranial pressure (ICP) values. We compare data from radiological imaging (CT and MRI) and clinical observations of patients with acute intracranial pathology. Downward transtentorial herniation was graded into four stages based on the caudal migration of the mammillary bodies and related structures; upward transtentorial herniation was classified into three progressive stages based on cerebellar and brainstem displacement. Midline shift (MLS) was correlated with GCS, pupillary changes, and ICP through comparative analysis of previous literature and observed patient data. A progressive relationship was observed between the degree of brain displacement and neurological decline. Increasing MLS correlated inversely with GCS and directly with anisocoria and elevated ICP. Downward and upward transtentorial herniations demonstrated distinct sequential imaging and clinical features, ranging from subtle diencephalic dysfunction to brainstem failure. Brain shift patterns — downward, upward, and lateral — are key indicators of neurological deterioration and prognosis in acute intracranial pathologies. Establishing a standardised correlation between imaging and clinical parameters enhances early recognition, facilitates surgical intervention, and improves patient outcomes.